HUBUNGAN TINGKAT PENGETAHUAN, SIKAP, DAN PERILAKU CUCI TANGAN PAKAI SABUN (CTPS) DENGAN KEJADIAN DIARE PADA SISWA SEKOLAH DASAR NEGERI - Suci Amalia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2026)
Diarrhea remains a public health problem among elementary school-aged children. Handwashing with soap, as part of a Clean and Healthy Lifestyle (PHBS), plays a crucial role in preventing infectious diseases such as diarrhea. Students' knowledge and attitudes toward handwashing with soap are key factors influencing hand hygiene behavior. This study used a Systematic Literature Review (SLR) approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to identify, select, and synthesize scientific evidence related to the relationship between knowledge, attitudes, and handwashing with soap behavior and diarrhea among public elementary school students. A literature search was conducted using Google Scholar, Semantic Scholar, PubMed, SINTA, and Scopus using the keywords